Skrinning Fitokimia dan Uji Sitotoksik Ekstrak Etanol Daun Diwoka (Piper macropiper Pennant) asal Wamena, Papua: Phytochemical Screening and Citotoxic Assay of Diwoka Leaves (Piper macropiper Pennant) Ethanolic Extract from Wamena, Papua - Tabuni, Frengchy Jalsan Charles; Tobi, Claudius Hendraman Boli; Dirgantara, Septriyanto; Pratiwi, Mustika Endah; Rumanasen, David Waranda; Appa, Felycitae Ekalaya; Barus, Andre Anusta (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Many plant species in Indonesia have not been identified and their utilities have not been studied. One of the traditional medicinal plants from Papua whose potential as a drug ingredient has not been widely explored is Diwoka (Piper macropiper Pennant). The study of bioactive compounds includes phytochemical and pharmacological approaches that begin with toxicity studies. This study aimed to determine the compounds contained in the ethanol extract of Diwoka leaves and its safety. The phytochemical screening method used was the reagent method and the cytotoxic test method used was the Brine Shrimp Lethality Test (BSLT). The results of the study showed that the ethanol extract of Diwoka leaves contains alkaloids, flavonoids, saponins, tannins and terpenoids. The cytotoxic test of the ethanol extract of Diwoka leaves on shrimp larvae showed a cytotoxicity potential included in the “toxic” category (LC50 = 79.33 ppm). This study is a preliminary study that shows that the ethanol extract of Diwoka leaves has secondary metabolite compounds that have the potential to have pharmacological activity and can be developed as natural medicine. Keywords: BSLT, Diwoka, Papua, Piper macropiper Pennant., Cytotoxic Abstrak Banyak spesies tanaman di Indonesia yang belum teridentifikasi dan diteliti manfaatnya. Salah satu tumbuhan obat tradisional asal Papua yang belum banyak dieksplorasi potensinya sebagai bahan obat adalah Diwoka (Piper macropiper Pennant). Studi senyawa bioaktif mencakup pendekatan fitokimia dan farmakologis yang diawali dengan studi toksisitas. Penelitian ini bertujuan untuk mengetahui senyawa terkandung dalam ekstrak etanol daun Diwoka serta keamanannya. Metode skrining fitokimia yang digunakan adalah metode reagen dan metode uji sitotoksik yang digunakan adalah Brine Shrimp Lethality Test (BSLT). Hasil penelitian menunjukkan bahwa ekstrak etanol daun Diwoka mengandung golongan senyawa alkaloid, flavonoid, saponin, tanin dan terpenoid. Uji sitotoksik ekstrak etanol daun Diwoka terhadap larva udang menunjukkan potensi sitotoksik dalam kategori “toksik” (LC50 = 79.33 ppm). Penelitian ini merupakan penelitian pendahuluan yang menunjukkan hasil bahwa ekstrak etanol daun Diwoka memiliki senyawa metabolit sekunder yang berpotensi memiliki aktivitas farmakologi dan dapat dikembangkan sebagai obat bahan alam. Kata Kunci: BSLT, Diwoka, Papua, Piper macropiper Pennant., Sitotoksik